2017
DOI: 10.3892/mmr.2017.8283
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced Rab11-family interacting protein�4�expression promotes migration and invasion of colon cancer and correlates with poor prognosis

Abstract: Rab11-family interacting proteins (Rab11‑FIPs) are associated with the progression of various tumors; however, their expression and clinical significance in colorectal cancer (CRC) remains largely undetermined. In this study, the clinical implications, functions and underlying mechanisms of Rab11‑FIP4 in CRC were investigated. Immunohistochemical analysis revealed that expression of Rab11‑FIP4 was significantly increased in human CRC tissues and correlated with poor prognosis of patients with CRC. Overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This suggests that Rab GTPase binding to PI4KIIIβ is not highly isoform selective and may be context dependent. It is noteworthy that Rab11 (126)(127)(128)(129), PI4KIIIβ (53) and ACBD3 (130) have all separately been reported to be upregulated in a range of cancers and this may imply that the entire PI4KIIIβ interactome at the Golgi is potentially oncogenic. These proteins can also mediate intracellular signalling; PI4KIIIβ and Rab11 co-operate to stimulate the activity of AKT in breast cancer cells although this occurs on endosomes rather than at the Golgi complex (53).…”
Section: Variety Of Pi4kiiiβ Roles and Binding Partners With Relevancmentioning
confidence: 99%
“…This suggests that Rab GTPase binding to PI4KIIIβ is not highly isoform selective and may be context dependent. It is noteworthy that Rab11 (126)(127)(128)(129), PI4KIIIβ (53) and ACBD3 (130) have all separately been reported to be upregulated in a range of cancers and this may imply that the entire PI4KIIIβ interactome at the Golgi is potentially oncogenic. These proteins can also mediate intracellular signalling; PI4KIIIβ and Rab11 co-operate to stimulate the activity of AKT in breast cancer cells although this occurs on endosomes rather than at the Golgi complex (53).…”
Section: Variety Of Pi4kiiiβ Roles and Binding Partners With Relevancmentioning
confidence: 99%
“…Some studies reported that Rab11-family interacting proteins (Rab11-FIPs) are associated with progression and poor survival in various tumors. Overexpression of Rab11-FIP4 was detected in colorectal cancer and pancreatic cancer tissues, it may predict poor survival of patients, and is also correlated with tumor progression [ 20 , 21 ]. Xu et al reported that Rab11-FIP2 upregulation enhanced invasion and migration in colorectal cells via regulation of matrix metalloproteinase 7 (MMP7) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the model organism zebrafish, RAB11FIP4 is expressed in neural tissues and is involved in the proliferation and differentiation of retinal tissues in the zebrafish retinal development process (19,20). RAB11FIP4 has also been shown to be perturbed in a variety of cancers, including pancreatic cancer, colon cancer and hepatocellular cancer (21)(22)(23).…”
Section: Ofmentioning
confidence: 99%